Dissecting the PI3K Signaling Axis in Pediatric Solid Tumors: Novel Targets for Clinical Integration - Loh, Amos H.; Brennan, Rachel C.; Lang, Walter H.; Hickey, Robert J.; Malkas, Linda H.; Sandoval, John A. (Frontiers in Oncology, 2013)
Children with solid tumors represent a unique population. Recent improvements in pediatric solid tumor survival rates have been confined to low- and moderate-risk cancers, whereas minimal to no notable improvement in survival have been observed in high-risk and advanced-stage childhood tumors. The development of novel therapeutic agents likely holds the key for patients with advanced disease that are frequently plagued with treatment failure and relapse. In the last years, biological advances have allowed for improved molecular characterization of signaling molecules and pathways contributing to tumor formation and growth. Exploiting these oncogenic cascades holds the promise for development of therapies that target alterations unique to an individual child’s tumor. An emerging target includes the phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway, which is activated in many adult solid cancers. Antagonists targeting this pathway have the potential to inhibit multiple key nodes and the use of selected rational combinations of these PI3K/Akt/mTOR inhibitors may be required to achieve the maximal cytotoxic response. Here, we examine the role of the PI3K/AKT/mTOR axis in selected pediatric solid tumors, review the pathway specific agents currently in clinical trials, and explore the ongoing challenges of the inhibition of this pathway in the clinical development of these agents in children.